Smart Learning from a Young Age : A Systematic Review of Digital Technology Integration for Cognitive Development - Adam, Nabil Fikri; Pramono, Suwito Eko; Yulianto, Arief; Subali, Bambang; Widiarti, Nuni (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to analyze the effectiveness of digital technology-based interactive learning media on cognitive enhancement in elementary education, thereby providing actionable insights to optimize teaching practices in the digital era. Employing a systematic literature review adapted from the PRISMA framework, the study conducted a structured search across three databases (Scopus, Web of Science, and Google Scholar) and identified 26 eligible articles that met predefined inclusion criteria related to digital technology use and quantitative cognitive outcome measures in elementary settings. The collected data were analyzed using content analysis, a systematic method for categorizing, quantifying, and synthesizing textual data to identify patterns, frequencies, and relationships across the included studies. The results revealed that digital technology integration positively impacts cognitive learning outcomes, with video and animation-based approaches being most prevalent (26.92%), followed by virtual/augmented reality, interactive applications, and educational games (19.23% each). The most significant advancements were observed in problem-solving and spatial reasoning skills, particularly when technologies incorporated constructivist principles, interactive engagement strategies, adaptive feedback mechanisms, and collaborative opportunities. This review confirms digital technology's effectiveness in enhancing elementary students' cognitive learning while emphasizing the importance of pedagogical approach and technology design; stakeholders should prioritize models that foster meaningful technology interactions emphasizing student empowerment, while future research should explore long-term cognitive effects and address limitations in study design heterogeneity and generalizability across diverse contexts.